Thyrotropin Releasing Hormone (TRH) may preserve pancreatic islet cell function: potential role in the treatment of diabetes mellitus - Luo, L-G; Jackson, Ivor (Acta Biomedica Atenei Parmensis, 2007)
Thyrotropin Releasing Hormone (TRH), first identified in the hypothalamus as a regulator of the Pituitary-Thyroid axis, has also been found in the b-cell of the pancreas co-localised with insulin. The significance of this association is emphasised by the report that the TRH knock-out (KO) mouse is hyperglycemic. These findings have led to speculation that TRH may have a physiologic role in the regulation of carbohydrate metabolism. To understand better the role of TRH in the pancreas, TRH was administered to rats rendered diabetic from streptozotocin damage to the islets of Langerhans. This resulted in almost complete normalisation of the profound hyperglycemia.TRH is capable of reversing Diabetes Mellitus (DM) in an experimental animal model, possibly by promoting neogenesis of beta cells through induction of adult stem cells in the pancreas. These studies point to a potential therapeutic role for TRH in the treatment of DM in man.